Simulation of the technique of pedaling of cyclists on the basis of visual control of the correspondence of the rhythm of angular movements in the links of a kinematic chain - Chermit, K. D.; Zabolotny, A. G.; Tikhonova, I. V.; Al Mahdi Shawkat Ezzat Abdullah (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the possibility of correcting the movements of the links of the kinematic chain of the motor apparatus of cyclists when performing the technique of circular pedaling based on visual control over the compliance of the realized movement with the ideal model of the power graph.